Accessible interactions 500: um jogo de tabuleiro híbrido inclusivo com realidade aumentada para auxiliar o ensino de química a alunos surdos e ouvintes - Fernandes, Natalia da Silva (2022)
Chemistry teaching presents many challenges. Most students consider it complex and abstract, making its learning difficult. In the context of students who are deaf, the challenges are even more significant since, for the most part, the teaching methodologies applied to Chemistry education are based on visual and oral elements. In this sense, accessible games are promising pedagogical tools to minimize this problem. Literature proves that games can impact the students' learning process due to increased engagement and arouse interest in learning school content in a more fun way. In this context, this study analyzes the application of an extended hybrid game with Augmented Reality (AR) in teaching chemistry to deaf and hearing students. In the systematic review of the literature carried out during this research, we observed a few solutions for using AR for teaching Science to deaf students. The vast majority of studies found use AR to teach sign language. Our research aims to contribute to the insertion of new methodologies in the teaching of Science for people who are deaf and to raise new reflections on this theme. A case study applying the game, through action research, was carried out in a state public school located in the city of Fortaleza, Ceará. 21 students participated, 6 deaf and 15 hearing. Two versions were applied, an analogue one, adapted from the Interactions 500 game, and a hybrid one, developed with analogue and hybrid elements from the analogue version. The results showed that the game was very well accepted by the students, although there was no significant difference between the pre and post tests applied when compared to the analog version of the game.